Phenomenological Model of Electrotechnical Systems Based on a Synchronous Generator With an Excitation System - Volodymyr Moroz; Yaroslav Paranchuk; Volodymyr Konoval; Oleksiy Kuznyetsov (Modelling and Simulation in Engineering)
We propose a variant of the application of a phenomenological approach using the “black box” concept to the modeling of electrotechnical systems. The method enables obtaining simplified models of a complex electrotechnical system based on a synchronous generator (SG) with an excitation system and an integral estimation of the accuracy of the reproduction of the original step response. The compromise between complexity and accuracy is the basis for obtaining the computer model of different orders utilizing the proposed method. The application of the proposed phenomenological approach is illustrated by the examples.